Genome-wide identification and comparative analyses of key genes involved in C4 photosynthesis in five main gramineous crops - Chen, Liang; Yang, Yang; Zhao, Zhangchen; Lu, Shan; Lu, Qiumei; Cui, Chunge; Parry, Martin A. J.; Hu, Yin-Gang (Frontiers in Plant Science, 2023)
Compared to C3 species, C4 plants showed higher photosynthetic capacity as well as water and nitrogen use efficiency due to the presence of the C4 photosynthetic pathway. Previous studies have shown that all genes required for the C4 photosynthetic pathway exist in the genomes of C3 species and are expressed. In this study, the genes encoding six key C4 photosynthetic pathway enzymes (β-CA, PEPC, ME, MDH, RbcS, and PPDK) in the genomes of five important gramineous crops (C4: maize, foxtail millet, and sorghum; C3: rice and wheat) were systematically identified and compared. Based on sequence characteristics and evolutionary relationships, their C4 functional gene copies were distinguished from non-photosynthetic functional gene copies. Furthermore, multiple sequence alignment revealed important sites affecting the activities of PEPC and RbcS between the C3 and C4 species. Comparisons of expression characteristics confirmed that the expression patterns of non-photosynthetic gene copies were relatively conserved among species, while C4 gene copies in C4 species acquired new tissue expression patterns during evolution. Additionally, multiple sequence features that may affect C4 gene expression and subcellular localization were found in the coding and promoter regions. Our work emphasized the diversity of the evolution of different genes in the C4 photosynthetic pathway and confirmed that the specific high expression in the leaf and appropriate intracellular distribution were the keys to the evolution of C4 photosynthesis. The results of this study will help determine the evolutionary mechanism of the C4 photosynthetic pathway in Gramineae and provide references for the transformation of C4 photosynthetic pathways in wheat, rice, and other major C3 cereal crops.